Relationship between weather parameters and risk of exertional heat injuries during military training - Beng Hoong Poon; Alexander Wilhelm Gorny; Kaiyuan Zheng; Wee Kiong Cheong (Singapore Medical Journal)
Introduction: The Singapore Armed Forces (SAF) collaborated with the Meteorological Service Singapore (MSS) to study the relationship between weather parameters and the incidents of exertional heat injury (EHI) to mitigate the risk of EHI in a practical manner. Methods: Data from the SAF's heat injury registry and MSS’ meteorological data from 2012 to 2018 were used to establish a consolidated dataset of EHI incidents and same-day weather parameters rank-ordered in deciles. Poisson regression modelling was used to determine the incidence rate ratios (IRRs) of the EHI, referencing the first decile of weather parameters. Two frames of analysis were performed - the first described the relationship between the weather parameters and the adjusted IRR for the same day (D), and the second described the relationship between the weather parameters and the adjusted IRR on the following day (D + 1). Results: For wet-bulb temperature, the IRR on D + 1 approximated unity for the first nine deciles but rose to 3.09 at the tenth decile. For dew-point temperature, the IRR on D + 1 approximated unity for the first nine deciles but rose to 3.48 at the tenth decile. By designating a single dew-point temperature cut-off at ≥25.1°C (transition between the ninth and tenth decile), the adjusted IRR on D + 1 was 2.26 on days with dew-point temperature ≥25.1°C. Conclusion: Integrating the data from the SAF and MSS demonstrated that a dew-point temperature ≥25.1°C on D correlates statistically with the risk of EHI on D + 1 and could be used to supplement the risk mitigation system.